Fundamental stage of development in table tennis (Polish experience) - Grycan, J. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
"FUNdamental stage" was defined as initial and basic stages of development of Primary School children. "The initial stage" was defined as FUNdamentals-1 which can be optimal for 6-8 years old children. "The basic stage" was defined as FUNdamentals-2 which can be optimal for 9-13 years old children. The FUNdamental stage is considered as the most important for learning-teaching table tennis single skills: grips, stance and basic ready positions, footwork steps, attacks, blocks, topspins, pushes, chops, serves, returns and their combinations. In 2009, Polish TTF prepared report on "the current state of training system in Poland". It was identified there that one of the weakest points was the low-quality training, coaching, and organization of initial and basic stages` usually run as imitating of "seniors` training model". On the basis of World literature (scientific papers, coaching books, films, documentaries etc.) and own experiences we have been building theoretical model of FUNdamental stage training system including: goals, designing and building teams, cultures, organizations, planning and monitoring training (physical, technical, tactical, mental), competition and recovery. Integral AQAL model was applied to organize all the knowledge. The theoretical model serves as the reference tool for action. On the basis of the theoretical model in 2009 the program "FUNdamentals, from dream to Mastery in table tennis" for children, coaches, managers, parents etc. was initiated. Until 2017 the program has been growing as constantly improved prototype on small scale including: over 200 whole-day workshops for coaches in 20 cities; over 500 two hours` skype teleseminars; over 150 coaches had finished the program FUNdamentals 1; over 30 coaches had finished FUNdamentals2; over 2000 children participated in the program; almost 1000 children attended over 20 training camps supervised by 100 coaches. In the process of continuous monitoring observation forms, skill observation charts, match statistical analysis, interviews with participants and experts, testing, questionnaires, after action reviews and other action research principles and tools are used. The purpose of this paper is (1) the first step of organizing all collected and recorded material and (2) presenting some key conclusions.